2003
DOI: 10.1021/es0304143
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Influence of Experimental Parameters on Formation of PCDD/F from Ash Derived from Fires of CCA-Treated Wood

Abstract: Ash residues from fires of radiata pine timber, both untreated and treated with chromated copper arsenate (CCA), were analyzed for the presence of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/F). Fire conditions were simulated using a cone calorimeter. The sensitivity of the magnitude and profile of PCDD/F in the ash under controlled experimental conditions were examined to gain an insight into the formation of PCDD/F in a system containing CCA. The total amount of PCDD/F increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…These results were further confirmed in the burning of household refuse by Lemiuex et al [15]. Other recent studies have shown that, the presence of the preservative CCA in pine, dramatically increased the ash dioxin concentration in the ash under fire conditions [16]. The enhanced formation was observed during the burnout of the wood char, after cessation of the flames.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…These results were further confirmed in the burning of household refuse by Lemiuex et al [15]. Other recent studies have shown that, the presence of the preservative CCA in pine, dramatically increased the ash dioxin concentration in the ash under fire conditions [16]. The enhanced formation was observed during the burnout of the wood char, after cessation of the flames.…”
Section: Introductionsupporting
confidence: 61%
“…The chemical characteristics of the timber sample have been published elsewhere [16]. O 2 and N 2 (Linde) used in the annealing experiments were of 99.999% purity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Baltic Sea region, a TeCP-TCP-PeCP mixture is a notable PCDF source , Bergkvist et al 2005. Burning wood that also contains CCA salts greatly increases TEQ DF yields (Tame et al 2003b). Other biocides of importance for cumulative emissions include 2,4,5-T.…”
Section: mentioning
confidence: 99%